2021
DOI: 10.1007/s10439-021-02784-1
|View full text |Cite|
|
Sign up to set email alerts
|

3D Printing for Cardiovascular Applications: From End-to-End Processes to Emerging Developments

Abstract: Abstract3D printing as a means of fabrication has seen increasing applications in medicine in the last decade, becoming invaluable for cardiovascular applications. This rapidly developing technology has had a significant impact on cardiovascular research, its clinical translation and education. It has expanded our understanding of the cardiovascular system resulting in better devices, tools and consequently improved patient outcomes. This review discusses the latest developments and future directions of genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 159 publications
0
21
0
Order By: Relevance
“…Many studies have identified absolute differences in accuracy between programs for specific software, [15,18], described 3D printing workflows for different applications [19][20][21], and discussed printing best practices [22,23]. In this paper, the behaviors of different mathematical algorithms used in ROI segmentation and refinement are reviewed to highlight key features that can affect the transformation of medical images into 3D printable models.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have identified absolute differences in accuracy between programs for specific software, [15,18], described 3D printing workflows for different applications [19][20][21], and discussed printing best practices [22,23]. In this paper, the behaviors of different mathematical algorithms used in ROI segmentation and refinement are reviewed to highlight key features that can affect the transformation of medical images into 3D printable models.…”
Section: Introductionmentioning
confidence: 99%
“…Device manufacturers and researchers with an interest in cardiovascular modelling, prediction and treatment of coronary artery disease can analyse this data directly or combine it with other available datasets. The smooth surface meshes and centrelines can be directly used for computational modelling 16 , directly 3D printed for experiments [18][19][20][21] , assist in developing and testing medical devices such as stents [22][23][24] , and can be used for Virtual Reality applications for education and training [25][26][27] . Moreover, our dataset allows for the development and benchmarking of new segmentation algorithms aiming to efficiently annotate the coronary arteries automatically as per ASOCA challenge 28 .…”
Section: Background and Summarymentioning
confidence: 99%
“…[41] Stereolithography, or SLA, as the oldest additive manufacturing (AM) technology, can be a costeffective option as it can achieve a relatively high resolution and a smoother surface finish as compared to cheaper alternatives like FDM. [43,44] Despite the superior surface quality that can be achieved with SLA 3D printing, it is not easy to avoid a certain level of surface roughness associated with the inherent layering process. [45][46][47] This is commonly referred to as the "stairstepping" effect and can hinder the optical transparency of 3Dprinted objects created from allegedly clear and transparent VAT resins.…”
Section: Introductionmentioning
confidence: 99%